High-safety composite ternary material and preparation method thereof
By covering lithium manganese iron phosphate on the ternary material and forming a solid solution, combined with fast ion conductor coating, the problem of poor thermal stability of the ternary material is solved, the conductivity and safety of the composite material are improved, and the performance improvement of high safety and high capacity is achieved.
Patent Information
- Application Number
- CN202411336891.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Due to its poor thermal stability and an increase in the proportion of unstable Ni3+, ternary materials are prone to react with moisture and carbon dioxide in the air, reducing their thermal stability. At the same time, conventional stirring processes have limited effect on improving the safety of ternary materials.
The ternary material is coated with lithium manganese iron phosphate, and the sintered nickel-cobalt-manganese lithium manganese is mixed by high-safe lithium manganese phosphate, and solid solution is formed by low-temperature sintering and bulk phase doping. The lithium manganese iron phosphate material is closely combined with the ternary material, and fast ion conductors are added simultaneously for coating.
It improves the conductivity and safety of composite materials, enhances its high safety and high capacity performance, and solves the problem of poor thermal stability of ternary materials.
Smart Images

Figure CN119542373A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a high-safety composite ternary material and a preparation method thereof. Background Art
[0002] In recent years, with the large-scale application of new energy vehicles, new energy vehicle fire accidents have aroused great concern in the society and become an important factor affecting the high-quality development of the new energy vehicle industry. The safety of electric vehicles needs to be solved urgently. As the mainstream positive electrode material, ternary materials are highly favored in the mid-to-high-end electric vehicle market due to their high energy density and excellent low-temperature activity.
[0003] However, due to its active layered lattice structure, the ternary material has poor thermal stability and decomposes at around 300°C, releasing oxygen molecules. As the nickel content increases, the proportion of unstable Ni3+ in the material increases, making it easy to react with moisture and carbon dioxide in the air, reducing its thermal stability.
[0004] The thermal decomposition temperature of lithium manganese iron phosphate is about 600℃, which is much higher than that of ternary materials. By mixing it with ternary materials, the safety performance of the materials can be balanced. However, the conventional mixing process has limited effect on improving the safety of ternary materials. In addition, due to the poor conductivity, rate performance and processing performance of lithium manganese iron phosphate, the conductivity and processing performance of the ternary materials are reduced after mixing. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a high-safety composite ternary material and a preparation method thereof.
[0006] In the first aspect, the present invention provides a high-safety composite ternary material, which is a high-safety composite material of a ternary material coated with lithium manganese iron phosphate, and the inner layer of the high-safety composite material is a ternary material LiaNibCocMndRxO2, wherein 0.8≤a≤1.05, 0.5≤b≤0.95, 0.05≤c≤0.35, 0≤d≤0.3, 0≤x≤0.15, b+c+d+x=1; R is at least one of Al, Ti, Mg, Sr, Y, W, B, Nb, La, Ta, Mo, and Zr.
[0007] Furthermore, the shell of the high-safety composite material is at least one of lithium iron manganese phosphate and a compound containing the element M; the element M is at least one of Al, Ti, Mg, Sr, Y, W, B, Nb, La, Ta, Mo, Zr, and a fast ion conductor.
[0008] In a second aspect, the present invention provides a method for preparing the high-safety composite ternary material according to any one of the first aspects, the preparation method comprising the following steps:
[0009] Mixing one or more of a ternary precursor, a lithium source, and a compound containing an R element to obtain a first mixed material;
[0010] The first mixed material is first sintered in an oxygen atmosphere, and then crushed to obtain a second mixed material;
[0011] The fast ion conductor material is uniformly dispersed in a LiOH aqueous solution, and then the second mixed material is added and ball milled to obtain a third mixed material;
[0012] The third mixed material, lithium manganese iron phosphate and a compound containing an M element are mixed and coated to obtain a fourth mixed material;
[0013] The fourth mixed material is subjected to a second sintering and then crushed to obtain a fifth mixed material;
[0014] The fifth mixed material and lithium iron manganese phosphate are mixed and coated to obtain the high-safety composite ternary material.
[0015] Furthermore, the working condition parameters of the first sintering include: a sintering temperature of 800° C.-940° C. and a sintering cycle of 9 h-32 h.
[0016] Furthermore, the working condition parameters of the second sintering include: a sintering temperature of 200° C.-500° C. and a sintering period of 3 h-10 h.
[0017] Furthermore, the ternary precursor includes Ni 0.67 Co 0.05 Mn 0.28 (OH)2.
[0018] Furthermore, the fast ion conductor material includes LATP.
[0019] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:
[0020] The embodiment of the present invention provides a high-safety composite ternary material and a preparation method thereof. The present invention uses high-safety lithium iron manganese phosphate to mix lithium nickel cobalt manganese oxide that has been sintered once or multiple times, and the coated mixed material is sintered at a low temperature. The solid solution is formed on the surface of the ternary material by bulk doping, and the lithium iron manganese phosphate material and the ternary material are tightly combined together. A fast ion conductor is simultaneously added for coating to improve the conductivity of the composite material, thereby ensuring the high safety and high capacity of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0023] Figure 1 This is a SEM characterization image of a high-safety composite ternary material provided in Example 1 of the present invention.
[0024] Figure 2 This is a SEM characterization image of a high-safety composite ternary material provided in Example 2 of the present invention.
[0025] Figure 3 This is a charge and discharge curve diagram of a high-safety composite ternary material provided in Example 1 of the present invention.
[0026] Figure 4 This is a charge and discharge curve diagram of a high-safety composite ternary material provided in Example 2 of the present invention.
[0027] Figure 5 This is a charge and discharge curve diagram of a high-safety composite ternary material provided in Comparative Example 1 of the present invention.
[0028] Figure 6 This is a charge and discharge curve diagram of a high-safety composite ternary material provided in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0031] In the first aspect, the present invention provides a high-safety composite ternary material, which is a high-safety composite material of a ternary material coated with lithium manganese iron phosphate, and the inner layer of the high-safety composite material is a ternary material LiaNibCocMndRxO2, wherein 0.8≤a≤1.05, 0.5≤b≤0.95, 0.05≤c≤0.35, 0≤d≤0.3, 0≤x≤0.15, b+c+d+x=1; R is at least one of Al, Ti, Mg, Sr, Y, W, B, Nb, La, Ta, Mo, and Zr.
[0032] The embodiment of the present invention provides a high-safety composite ternary material. The present invention uses high-safety lithium iron manganese phosphate to mix lithium nickel cobalt manganese oxide that has been sintered once or multiple times, and the coated mixed material is sintered at low temperature. The solid solution is formed on the surface of the ternary material by bulk doping, and the lithium iron manganese phosphate material and the ternary material are tightly combined together. A fast ion conductor is simultaneously added for coating to improve the conductivity of the composite material, thereby ensuring the high safety and high capacity of the composite material.
[0033] A high-safety composite material of lithium manganese iron phosphate coated with ternary materials, wherein the inner layer is the ternary material LiaNibCocMndRxO2, wherein 0.8≤a≤1.05, 0.5≤b≤0.95, 0.05≤c≤0.35, 0≤d≤0.3, 0≤x≤0.15, b+c+d+x=1; R is one or more compounds containing elements such as Al, Ti, Mg, Sr, Y, W, B, Nb, La, Ta, Mo, Zr, etc., and the lithium source involved adopts lithium salts of conventional types in the industry. The outer shell is lithium manganese iron phosphate, at least one of the compounds containing M elements (Al, Ti, Mg, Sr, Y, W, B, Nb, La, Ta, Mo, Zr, etc.), and a fast ion conductor (primary particles 200-800nm).
[0034] 1. Mix one or more of the ternary precursor, the lithium source, and the compound containing the R element at high speed;
[0035] 2. Sinter the mixed materials in an oxygen atmosphere at a sintering temperature of 800°C-940°C and a sintering period of 9h-32h, and crush the sintered materials;
[0036] 3. Weigh 0.1wt%-5wt% LiOH and prepare a solution with deionized water (0.5-1.0:1), evenly disperse 0.5wt%-1.5wt% fast ion conductor material (such as LATP fast ion conductor material, i.e. lithium aluminum titanium phosphate) in the LiOH solution, and then mix the intermediate with the prepared solution. While ball milling, the particle size of the fast ion conductor can be reduced and the coating effect can be improved;
[0037] 4. The ball-milled material is coated with a small amount of lithium iron manganese phosphate and at least one compound containing the element M (M is Al, Ti, Mg, Sr, Y, W, B, Nb, La, Ta, Mo, Zr, etc.) in a mixer;
[0038] 5. Sinter the coated material in compressed air or inert protective gas at a sintering temperature of 200°C-500°C and a sintering period of 3h-10h;
[0039] After the secondary sintered material is crushed, it is coated with 8wt%-15wt% lithium iron manganese phosphate in a fusion machine, and the lithium iron manganese phosphate is evenly coated on the surface of the material to obtain a high-safety composite material.
[0040] It should be noted that the component raw materials involved in the high-safety composite ternary material and the preparation method thereof provided in the embodiments of the present invention, unless otherwise specified or specified, can be directly commercially available products or homemade using existing public preparation methods; at the same time, the steps and parameters involved, unless otherwise specified or specified, can be carried out according to the existing processing technology of high-safety composite ternary materials or directly using existing equipment, and the present invention document will not elaborate on them one by one.
[0041] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0042] Example 1
[0043] This example provides a high-safety composite ternary material, including the following steps:
[0044] 1. Select Ni as the precursor 0.67 Co 0.05 Mn 0.28 (OH)2, according to Li / M=1.02, the precursor, lithium carbonate, oxides containing Zr, Y, W, and phosphate containing La are mixed in a high-speed mixer;
[0045] 2. Sinter the mixed materials in an oxygen atmosphere at 935°C for 10-15h, and crush the sintered materials;
[0046] 3. Prepare a 1:2 solution with 2.2wt% LiOH and deionized water, disperse 1wt% LATP in the solution, and then ball-mill the finely crushed material and the prepared solution for 30 minutes;
[0047] 4. The ball-milled material is mixed and coated with 1.5wt% lithium manganese iron phosphate and oxides containing Al, Ti and B at high speed;
[0048] 5. Sinter the coated material in compressed air at 470°C for 9 hours;
[0049] 6. The secondary sintered material is crushed, sieved, and then 13.5 wt% lithium manganese iron phosphate is added for fusion coating.
[0050] The SEM characterization of the high-safety composite ternary material obtained in this example is shown in Figure 1 shown.
[0051] Example 2
[0052] This example provides a high-safety composite ternary material, including the following steps:
[0053] 1. Select Ni as the precursor 0.67 Co 0.05 Mn 0.28 (OH)2, according to Li / M=1.01, the precursor, lithium carbonate, oxides containing Zr, Y, W, and phosphate containing La are mixed in a high-speed mixer;
[0054] 2. Sinter the mixed materials in an oxygen atmosphere at 935°C for 10-15h, and crush the sintered materials;
[0055] 3. Prepare a 1:2 solution with 3 wt% LiOH and deionized water, disperse 0.5 wt% LATP in the solution, and then mix the finely crushed material with the prepared solution by ball milling for 30 minutes;
[0056] 4. The ball-milled material is mixed and coated with 1.5wt% lithium manganese iron phosphate and oxides containing Al, Ti and B at high speed;
[0057] 5. Sinter the coated material in compressed air at 470°C for 9 hours;
[0058] 6. The secondary sintered material is crushed, sieved, and then 13.5 wt% lithium manganese iron phosphate is added for fusion coating.
[0059] The SEM characterization of the high-safety composite ternary material obtained in this example is shown in Figure 2 shown.
[0060] Comparative Example 1
[0061] This example provides a high-safety composite ternary material, which is coated by a dry method and includes the following steps:
[0062] 1. Select Ni as the precursor 0.67 Co 0.05 Mn 0.28 (OH)2, according to Li / M=1.02, the precursor, lithium carbonate, oxides containing Zr, Y, W, and phosphate containing La are mixed in a high-speed mixer;
[0063] 2. Sinter the mixed materials in an oxygen atmosphere at 935°C for 10-15h, and crush the sintered materials;
[0064] 3. Use 2.2wt% LiOH, 1wt% LATP, 1.5wt% lithium manganese iron phosphate, and oxides containing Al, Ti, and B for high-speed mixed coating;
[0065] 4. Sinter the coated material in compressed air at 470°C for 9 hours;
[0066] 5. The secondary sintered material is crushed, sieved, and then 13.5 wt% lithium manganese iron phosphate is added for fusion coating.
[0067] In this case, dry coating of LATP was used, and there was obvious residue after sieving with 400 mesh. The result of the withholding test was lower than that of wet coating.
[0068] Comparative Example 2
[0069] This example provides a high-safety composite ternary material, using a conventional lithium ratio, including the following steps:
[0070] 1. Select Ni as the precursor 0.67 Co 0.05 Mn 0.28 (OH)2, according to Li / M=1.05, the precursor, lithium carbonate, oxides containing Zr, Y, W, and phosphate containing La are mixed in a high-speed mixer;
[0071] 2. Sinter the mixed materials in an oxygen atmosphere at 935°C for 10-15h, and crush the sintered materials;
[0072] 3. Disperse 1wt% LATP in 4wt% deionized water, and then mix the finely crushed material with the prepared solution by ball milling for 30 minutes;
[0073] 4. The ball-milled material is mixed and coated with 1.5wt% lithium manganese iron phosphate and oxides containing Al, Ti and B at high speed;
[0074] 5. Sinter the coated material in compressed air at 470°C for 9 hours;
[0075] 6. The secondary sintered material is crushed, sieved, and then 13.5 wt% lithium manganese iron phosphate is added for fusion coating.
[0076] Test Case
[0077] In this example, the composite ternary materials provided in Examples 1 to 2 and Comparative Examples 1 to 2 were tested for performance. The test results are as follows: Figure 3-Figure 6 As shown in Table 1, Table 2 and Table 3.
[0078] Table 1
[0079]
[0080]
[0081] Table 2
[0082]
[0083] Table 3
[0084]
[0085] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0086] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A high-safety composite ternary material, characterized in that: The high-safety composite ternary material is a high-safety composite material of lithium manganese iron phosphate coated with a ternary material, and the inner layer of the high-safety composite material is a ternary material LiaNibCocMndRxO2, wherein 0.8≤a≤1.05, 0.5≤b≤0.95, 0.05≤c≤0.35, 0≤d≤0.3, 0≤x≤0.15, b+c+d+x=1; R is at least one of Al, Ti, Mg, Sr, Y, W, B, Nb, La, Ta, Mo, and Zr.
2. The high-safety composite ternary material according to claim 1, characterized in that: The shell of the high-safety composite material is at least one of lithium manganese iron phosphate and a compound containing the M element; the M element is at least one of Al, Ti, Mg, Sr, Y, W, B, Nb, La, Ta, Mo, Zr, and a fast ion conductor.
3. A method for preparing the high-safety composite ternary material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: Mixing one or more of a ternary precursor, a lithium source, and a compound containing an R element to obtain a first mixed material; The first mixed material is first sintered in an oxygen atmosphere, and then crushed to obtain a second mixed material; The fast ion conductor material is uniformly dispersed in a LiOH aqueous solution, and then the second mixed material is added and ball milled to obtain a third mixed material; The third mixed material, lithium manganese iron phosphate and a compound containing an M element are mixed and coated to obtain a fourth mixed material; The fourth mixed material is subjected to a second sintering and then crushed to obtain a fifth mixed material; The fifth mixed material and lithium iron manganese phosphate are mixed and coated to obtain the high-safety composite ternary material.
4. The method for preparing a high-safety composite ternary material according to claim 3, characterized in that: The working condition parameters of the first sintering include: sintering temperature of 800° C.-940° C., and sintering cycle of 9 h-32 h.
5. The method for preparing a high-safety composite ternary material according to claim 3, characterized in that: The working condition parameters of the second sintering include: sintering temperature of 200° C.-500° C., and sintering period of 3 h-10 h.
6. The method for preparing a high-safety composite ternary material according to claim 3, characterized in that: The ternary precursor includes Ni 0.67 Co 0.05 Mn 0.28 (OH)2.
7. The method for preparing a high-safety composite ternary material according to claim 3, characterized in that: The fast ion conductor material includes LATP.
Citation Information
Patent Citations
Preparation method of composite coated ternary positive electrode material
CN112794372A
Preparation method of high-nickel ternary positive electrode material
CN114220965A
Preparation method of ternary positive electrode material
CN115092977A
Positive electrode composite material and preparation method and application thereof
CN116190602A
Lithium manganese iron phosphate coated ternary composite material as well as preparation method and application thereof
CN116598442A